Wind Erosion and its Control in Arid North-West India - Venkateswarlu, J; Kar, Amal (Annals of Arid Zone, 2016)
Wind erosion is a major problem in the arid sandy tract of north-west India, especially in west Rajasthan. To understand the spatial pattern of wind erosion in the region, wind erosivity and erodibility of the terrain have been worked out. which suggest a westward increase in the erosivity with decreasing rainfall and increasing wind velocity. The pattern of erodibility cuts across this gradient. Currently man is the most important agent for acceleration of aeolian process, although the nature of sand reactivation is dependent more on the pattern of erosivity. Many of the problems can be tackled through effective technology intervention like vegetative propagation in the sandy terrain, plantation of dunes, etc., for which the Central . Arid Zone Research Institute. Jodhpur has the required expertise. Mechanical methods of control are not very popular, but have their appeal in specific areas. For the success of any technology intervention, however, people's participation will be necessary.